Optimizing electromagnetic interference shielding of carbon nanofibers reinforced nylon 6, 6 nanocomposite films in terahertz range. Issue 18 (24th February 2023) - Arooj, Nooria; Mumtaz, Muhammad; Rehman, Abdur; Ahmad, Izhar; Khan, Sabih; Shah, Attaullah; ul Hassan, Mahmood; Raffi, Muhammad
Abstract: The widespread development and usage of electrical and electronic devices in THz frequency band has instigated great concerns regarding the anticipated functioning of devices. The world is in dire need to develop tunable shielding materials which are not only field functional but could also provide shielding against undesired electromagnetic signals by absorption as the primary mechanism. In this work, nylon 6, 6 based hybrid nanocomposite films loaded with 0–50 wt% CNFs have been prepared on the cellulosic substrates by air spray coating technique. XRD and FESEM results have established formation of crystalline films having homogeneously distributed CNFs in the polymer matrix leading to formation of an efficient conductive network. IV measurements demonstrate a significant rise in the dc conductivity in the polymer nanocomposite samples with the gradual increase of CNF content in comparison to the pristine sample. Interestingly, sample containing 50 wt% CNFs has shown dc conductivity value of 0.03 Scm −1 while shielding effectiveness (SE) of 44 dB obtained through THz‐TDS. The results hold a distinctive position in these samples which have outperformed at a very low thickness of 570 μm as compared to the results obtained by many other novel polymer composites and present themselves a light weight field functional high THz absorption materials. Abstract : THz shielding of spray coated CNFs loaded nylon6, 6 polymer composite films.